Plug back into work, safely: Job reattachment, leader safety commitment, and job engagement in the COVID-19 pandemic. - Yuan, Zhenyu; Ye, Zhuxin; Zhong, Meng (Journal of Applied Psychology, 2021)
With many employees returning to work after lockdowns and quarantines in the current COVID-19 pandemic, research that seeks to identify effective ways to help them regain focus at work is warranted. However, the small body of applied psychology literature on large-scale disruptive events has paid insufficient attention to this important topic. Further, different from acute events (e.g., disasters), the ongoing pandemic poses an additional challenge for organizations as they seek to effectively protect employees' job engagement from health and safety threats in the workplace. To address these gaps, we drew from job reattachment research and investigated it as an important antecedent of job engagement for employees returning to work. Moreover, we incorporated leader safety commitment as a moderator that can strengthen the effectiveness of job reattachment in enhancing job engagement. We further linked engagement to work withdrawal, use of personal protective equipment (e.g., wearing a mask), and task performance to underscore the downstream implications of job reattachment. To test our research model, we collected multiwave, multisource data from the original epicenter of the COVID-19 pandemic-Wuhan, China-where many employees were returning to work. The results provide strong support for our model. In addition to extending research on large-scale disruptive events, the current study has important implications for organizations and employees in the COVID-19 pandemic. (PsycInfo Database Record (c) 2021 APA, all rights reserved).